Religious Folk-Songs of the Southern Negroes - Odum, Howard W. (American Journal of Religious Psychology and Education, 1909)
This is a reprint of Odum's 1909 dissertation for Clark University which first appeared in the American Journal of Religious Psychology and Education. This reprint seems to have been done in the same year and is thus one of Odum's earliest publications. This book has been more recently reprinted but this is the original. Odum was only 26 at the time he wrote this work based on his extensive field work for a number of years. He would later publish a number of important early works on African-American music.
Odum, Howard W. "Religious Folk-Songs of the Southern Negroes." PhD. diss., Clark University. *American Journal of Religious Psychology and Education,* vol.3, pp 265-365. July, 1909. http://hdl.handle.net/10428/2992.
Keywords: Folk songs; Gospel music--United States; African Americans--Music; Dissertations